Membrane-mediated activity of local anesthetics - Grage, Stephan L.; Culetto, Anke; Ulrich, Anne S.; Weinschenk, Stefan (Molecular pharmacology, 2021)
The activity of local anesthetics (LAs) has been attributed to the inhibition of ion channels, causing anesthesia. However, there is a growing body of research showing that LAs act on a wide range of receptors and channel proteins far beyond simple analgesia. The current concept of ligand recognition may no longer explain the multitude of protein targets influenced by LAs. We hypothesize that LAs can cause anesthesia without directly binding to the receptor proteins just by changing the physical properties of the lipid bilayer surrounding these proteins and ion channels based on LAs’ amphiphilicity. It is possible that LAs act in one of the following ways: They 1) dissolve raft-like membrane microdomains, 2) impede nerve impulse propagation by lowering the lipid phase transition temperature, or 3) modulate the lateral pressure profile of the lipid bilayer. This could also explain the numerous additional effects of LAs besides anesthesia. Furthermore, the concepts of membrane-mediated activity and binding to ion channels do not have to exclude each other. If we were to consider LA as the middle part of a continuum between unspecific membrane-mediated activity on one end and highly specific ligand binding on the other end, we could describe LA as the link between the unspecific action of general anesthetics and toxins with their highly specific receptor binding. This comprehensive membrane-mediated model offers a fresh perspective to clinical and pharmaceutical research and therapeutic applications of local anesthetics. - SIGNIFICANCE STATEMENT Local anesthetics, according to the World Health Organization, belong to the most important drugs available to mankind. Their rediscovery as therapeutics and not only anesthetics marks a milestone in global pain therapy. The membrane-mediated mechanism of action proposed in this review can explain their puzzling variety of target proteins and their thus far inexplicable therapeutic effects. The new concept presented here places LAs on a continuum of structures and molecular mechanisms in between small general anesthetics and the more complex molecular toxins.